Design and Development of Intelligent Logistics Tracking System Based on Computer Algorithm - Dong, Demei Gao (Bright Institute, 2023)
The logistics industry has experienced significant growth alongside the progress of the social economy. In this research article, the aim is to create a sophisticated tracking system for the logistics sector by utilizing computer technology. The primary focus is on developing an intelligent inventory decision support system. The article introduces two key algorithms: one that detects the integrity of goods packaging and another that identifies the behavior and posture of goods using a three-dimensional acceleration sensor. Furthermore, the article describes the workflow of the system and provides a thorough design for implementation in a real cabin environment. To validate the effectiveness of the system, experiments are conducted, and its performance is evaluated. The continuous advancement of the logistics industry, driven by the growth of the social economy, has prompted the need for innovative solutions. This scholarly article aims to address this demand by proposing the development of an intelligent logistics tracking system empowered by computer technology. The primary objective is to create an intelligent inventory decision support system capable of optimizing inventory management processes. To achieve this, the article presents two crucial detection algorithms. The first algorithm focuses on assessing the integrity of goods packaging, ensuring that goods remain intact throughout the logistics journey. The second algorithm leverages a three-dimensional acceleration sensor to analyze the behavior and posture of goods during transportation. The article also provides a comprehensive overview of the system's workflow, detailing the various steps involved. Furthermore, to validate the practical applicability and efficiency of the system, a detailed design is executed in a real cabin environment. Through rigorous experimentation and performance evaluation, the article aims to ascertain the effectiveness of the proposed system in enhancing logistics operations.